PENGARUH INFORMASI POSITIF DAN NEGATIF PADA KONDISI PASAR BULLISH DAN BEARISH TERHADAP RETURN SAHAM (Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia) - Cahyadi, Cahyadi Agung; Martono, Cyrillius; Prabowo, F.X. Agus Joko Waluyo (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2017)
The purpose of this research is to test the market reaction shown by the existence of abnormal return to the change of cash dividend distribution in two different condition that is bullish and bearish market condition in period 2014-2016. The sample used in this research is 165 announcement of dividend up and down. The method used in this study is the analysis of event study to analyze the market reaction in the observation period that is 11 days around the date of the announcement of cash dividends. The results of this study indicate that in bullish or bearish condition, the increase and decrease of cash dividend to be distributed has no impact on market reaction. Therefore, this study does not support signaling theory.